Utilização da robótica educacional livre por meio da aprendizagem por projetos: um estudo no curso técnico em Informática do IFPA/campus Santarém - CRUZ, Rodrigo Sousa da (2017)
With the publication of Decree 5.154/04, became possible to offer technical courses in the modality of integrated secondary education to professional education. It emerges as an alternative to overcome the dichotomy of existing formations between general and professional education. One of its great challenges is to implement, in fact, its integrated character. This research aims to investigate the benefits of applying a free robotic learning project in the context of the Technical Course in Computer Science / Integrated High School education of IFPA/Campus Santarém (CTI / EMI). From the works of Kuenzer (2000, 2003), Frigotto, Ciavatta and Ramos (2005), Frigotto (2005) and Santomé (1998), some aspects about the historical relationship between education and work were raised, emphasizing the dichotomy between general and professional formation. By associating free educational robotics with the pedagogy of projects, alternatives were sought that favor the protagonism of the students, regarding the proposition of solutions to a problem of their realities, and also what skills can be developed by them in this approach. In this sense, the works of Moura and Barbosa (2011), Bender (2014), Nogueira (2007) and Oliveira (2006) were taken as the basis for Project Pedagogy, and Papert (2008), Blikstein (2013) and Cesar (2009, 2013), regarding open source educational robotics and constructionism. The methodological path of this investigation was divided into two stages. The first step was to plan the action and comprises an exploratory bibliographic research. It gave rise to a plan of action, which guided the implementation of the Integrated Project (PI) "Robótica Educacional Livre do IFPA/Campus Santarém". Its execution concerns the second stage of the methodological path, where a case study was applied, which subsidized the application of several data collection instruments. The PI allowed the formation of three teams. Each one proposed a robotic solution whose themes should be associated to a problem associated with the reality of the students. In this way, this work proposes to investigate how the free educational robotics, through learning by projects, can be used as a resource that helps in the critical formation of a group of students of the CTI/EMI? To answer this question were used the technique of contents analysis of Bardin (2011), which were indicated three categories of analysis: critical formation, perceived skills and interdisciplinarity.